2003
DOI: 10.1136/gut.52.1.116
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for recurrent bile duct stones after endoscopic papillotomy

Abstract: Background:The long term outcome of endoscopic papillotomy (EPT) is not well known. The aims of this study were to clarify the clinical course of post-EPT patients and to detect predictors for bile duct stone recurrence. Methods: A total of 1042 consecutive patients who underwent EPT for bile duct stones from December 1975 to September 1998 were prospectively followed up. Patients were divided into four groups according to gall bladder (GB) status: "acalculous GB" group, "calculous GB" group, "cholecystectomy"… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
171
6
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(191 citation statements)
references
References 30 publications
11
171
6
3
Order By: Relevance
“…Greater incidence of ascending infection and lower CBD stone density may be possible explanations, but this needs to be studied further. [16][17][18]. The present study demonstrated that CBD diameter and EPLBD more than 10 mm were independent factors related to recurrence upon multivariate analysis.…”
Section: Discussionmentioning
confidence: 70%
“…Greater incidence of ascending infection and lower CBD stone density may be possible explanations, but this needs to be studied further. [16][17][18]. The present study demonstrated that CBD diameter and EPLBD more than 10 mm were independent factors related to recurrence upon multivariate analysis.…”
Section: Discussionmentioning
confidence: 70%
“…Interestingly, a dilated CBD was identified as a risk factor of bile duct stone recurrence after endoscopic papillotomy by previous studies [4,6] . However, our results should be interpreted from a different point of view because the pathogenesis of CBD stone recurrence and the development of acute cholecystitis differ.…”
Section: Discussionmentioning
confidence: 85%
“…The high success rate and safety of this modality have been well established by a number of studies [1][2][3][4][5] . Because gallstones may pass from the gallbladder (GB) into the CBD, calculous GB is considered to be one of the risk factors for the recurrence of bile duct stones after sphincterotomy [4,6] . Some studies have compared the results of the wait-andsee policy and prophylactic cholecystectomy to prevent biliary complications but arrived at contradictory results [7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…Additional reflux caused by contractional malfunction of the sphincter leads to the reflux of gastrointestinal juice into the bile duct, bacterial infection of the bile duct and formation of pigment bile duct stones. 2,[5][6][7][8] The dysfunction of the SO (decrease of the pres sure) has been demonstrated in manometric studies. 9,10 The clinical result of the dysfunction of SO is the formation of CBD stones, infection (cholangitis) or pancreatic disease.…”
Section: Discussionmentioning
confidence: 99%